The Role of Teacher Leaders in School Improvement Program: The case of Atse Naod primary school. - Shimekit , Tesfamariam; Tizazu, Getnet (Advances in Social Sciences Research Journal, 2021)
The purpose of this study was to understand teacher leaders’ role in school improvement program. More specifically, examined how teacher leaders formally or informally lead school improvement; what potential challenges they face when attempting to lead school improvement; and what strategies /mechanisms they employ to improve teacher leadership role in school improvement process were the basic questions of the study. In-depth interviews with five teacher leaders and field notes were used to collect data. The data were tape recorded and then transcribed. Categories themes and patterns from data i.e. inductive analysis were used for data analysis. The findings revealed that, teacher leaders lead school improvement by different methods like collaboration, effective planning, and experience sharing, influencing others by their hardworking habit and, communicating with school community. Besides, teacher leaders face different challenges in leading school improvement such as lack of leadership and management skill, time constraints and absence of recognition and incentive. In sum, the school improvement process is not being led by teacher leaders due to different challenges. Therefore, education leaders should enhance teacher leadership by promoting and supporting teacher leadership role and Policy makers should develop a platform for teacher leadership to enhance teacher leaders’ role in school improvement program.